InVesa 1.0: The Conceptual Framework of Interactive Virtual Academic Advisor System based on Psychological Profiles - Ahmad Sofian, Shminan; Lee, Jun Choi; Mohd Hardyman, Bin Barawi; Wan Norizan, Wan Hashim; Harisson, Andy (IEEE, 2021)
Interactive Virtual Academic System Prototype (InVesa) is a conceptual automated system dedicated to students where a theory of personality test, Holland Code (RIASEC) is integrated to aid students in selecting the ideal elective subjects for their Cognitive Science course. With InVesa, rather than giving alerts to academic advisors, students are assigned personalized advice by the system on the recommended elective subjects based on their RIASEC result. A student may choose to accept a list of subjects' recommendations from the system or to retake the RIASEC test until they are satisfied with the suggested subjects provided by the system. In addition, students with less time meeting their academic advisors to consult on their subject enrolment may avoid general issues that are common in the standard appointment registration system, such as multiple registrations and long queues when scheduling an appointment. It can be concluded that the proposed application meets the requirements. The proposed application provides a convenient and efficient solution to gain the required information and will benefit the targeted users, which achieves and fulfills the forth of Sustainable Development Goals (SDG) of Quality Education for better education quality for all in terms of gender, age and status.